Предмет: Алгебра,
автор: alvinaskirdonova
помогите пожалуйста
умножение одночлена на многочлен
9a (5a - 4b²) =
-n(p+ 2n-11)=
(7x² +3x-6)×(-1/3x³)=
(4m² -11m+8)×0,4m=
Ответы
Автор ответа:
1
(а-4)^2-2a(5a-4) == a^2 -2*a*4+4^2 - 2a(5a-4) == a^2 -8a+16 -10a^2 +8a = << -8a+8a сокращаются= 9a^2 + 16 вроде так
Автор ответа:
0
45a2-36ab2
-np+-2n2+11n
-np+-2n2+11n
Похожие вопросы
Предмет: Математика,
автор: aydan2002
Предмет: География,
автор: shoem
Предмет: Алгебра,
автор: ksenyaKandalenceva
Предмет: Физика,
автор: moskaliov